Effects of varying particle size, resin and wax content on the properties of homogenous melamine urea formaldehyde particleboard from bamboo (Gigantochloa scortechinii) / Jamaludin Kasim, Abd. Jalil Ahmad dan Shaikh Abdul Karim Yamani - Kasim, Jamaludin; Ahmad, Abd. Jalil Ahmad; Yamani, Shaikh Abdul Karim Yamani (2004)
In the study of high moisture resistant particleboard from bamboo (Gigantochloa scortechinii), homogenous melamine urea-formaldehyde particleboard was produced. An increase in resin content was accompanied by an increase in the mechanical and improvement in water absorption and thickness swelling properties. Varying the particle sizes also showed differences in the mechanical and physical properties. Wax addition increased the board stability towards water exposure but decreased the mechanical properties of the boards. All boards surpassed the minimum requirement of the BS for the mechanical and physical properties. Particles from three-year-old Gigantochloa scortechinii were suitable for the making of homogenous urea-formaldehyde particleboard.